The Influence of Work Enviroment, Work Motivation and Training on Employee Performance in PT. Lima Benua Medan - Dema Claudia Yosephine Simanjuntak; Richardo Thomas Halim; Reynoldo Thomas Halim (Kusuma Negara Business School, 2021)
Assessing and observing the impact of the work environment, motivation, and training on the performance of PT. Lima Benua both individually and simultaneously to realize the objectives of this research. Quantitative descriptive is this type of research, with explanatory nature. The population of all employees of PT. Lima Benua were 36 people. A sample of 36 people, obtained by the saturated sampling technique. Research data obtained by conducting interviews, questionnaires, and documentation studies. The data analysis method is multiple linear regression, coefficient of determination test, partial test, and simultaneous test. The result is that the work environment, motivation, and training individually and simultaneously affect the performance of PT. Lima Benua. 78.5% of the variation of employee performance variables that can be studied with the independent variables of work environment, motivation, and training, 21.5% of the excess of the coefficient of determination test is examined outside the research variables.